Skills-specific tactical fight control algorithms in judo - Levitsky, A. G.; Rudenko, G. V.; Simakov, D. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze skills-specific tactical decision making algorithmic models of competitive performance in modern judo.